Thermal performance enhancement in a hexagonal cavity filled with hybrid nanofluid and a steering-shaped insertion - Bijan Krishna Saha; Goutam Barai; Nithan Majumdar; Md. Aslam Hossain; Goutam Saha; Goutam Saha; Suvash C. Saha (Frontiers in Energy Research, 2025)
BackgroundSteering-shaped obstacles are extensively used in various thermal engineering applications, including heat exchangers, transformers, semiconductors, microelectronics, chemical sensors, air-cooled engines, gas turbines, automotive radiators, and hydrogen fuel cells.AimsThe main goal of this study was to examine how key dimensionless parameters—such as the Reynolds number (Re), Richardson number (Ri), Hartmann number (Ha), Nusselt number (Nu), Bejan number (Be), and magnetic field angle (γ)—affect the heat transfer, fluid flow, and entropy generation in a hybrid nanofluid (TiO2−Cu−H2O) system. A mixed convection flow is analyzed inside a hexagonal cavity containing a heated steering-shaped obstacle. The cavity has two moving walls that drive the flow, whereas a magnetic field is applied at an angle. The focus is to reduce entropy generation and enhance thermal performance, which is important for improving the efficiency of advanced cooling systems.Method and validationsThe governing equations and boundary conditions are solved using the Galerkin weighted residual finite element method, with extensive validation against existing results to ensure the accuracy of the findings.ParametersIn the study, we investigate a range of parameters: nanoparticle concentration (φ) varying from 1% to 5%, Re from 1 to 300, Ha from 0 to 60, Ri from 0.1 to 10, and γ ranging from 0° to 90°.ResultsIn the study, we show that lid-driven motion of the top and bottom walls, along with a steering-shaped heated obstacle, enhances heat transfer (HT) and reduces entropy generation(Egen). Thermal performance improves with increasing Ri and Re but decreases with increasing Ha. For fixed Re = 300, at the highest magnetic field strength (Ha = 60), the HT rate reaches its minimum, exhibiting a 22.41% decrease relative to the no magnetic-field condition (Ha = 0). An increase in the Ri number leads to a 68.76% enhancement in thermal performance. At a fixed Ri=10, increasing the Re number from 1 to 300 leads to a 263.83% enhancement in thermal performance. The addition of TiO2−Cu−H2O hybrid nanofluid (HNF) further enhances thermal performance.ConclusionIn the study, we reveal that mixed-convection (MC) HNF and heated steering-shaped obstacles play a significant role in enhancing HT and reducing Eavg within the cavity.